Community Services on Website Development for Agripina Kindergarten Surabaya as a School Profiling Media - Eka Prakarsa Mandyartha; Eva Yulia Puspaningrum (Future Science, 2022)
Agripina Kindergarten Surabaya, located in Rungkut District, Surabaya City, is an educational institution for pre-school education for early childhood and kindergarten. Agripina Kindergarten as an educational institution must be active in advancing the institution. The progress of educational institutions can be seen from the effectiveness in promoting schools to the community so that they can attract public interest in schools to these educational institutions. The rapid development of technology can be utilized by institutions in building relationships with the community and providing various information and facilities related to schools. This can be realized through the school website. The school website serves as a school profiling media. for that required the ability of human resources or teachers there in creating and managing web applications. Through the website as a school profiling medium, the identity of the school, the school's vision and mission, curriculum, teachers, student activities, and school facilities and infrastructure can be displayed. Through community service activities carried out by a team of lecturers from UPN veterans of East Java, they will provide training in the field of web creation and management for teachers there. Creating a basic school website through WordPress is taught through this activity, which serves as a type of training. WordPress is a website-based Content Management System (CMS) platform that can be operated by the public, without having special skills in the field of information technology such as programming. This community service activity aims to provide training to Agripina Kindergarten teachers to have the insight and skills to build a simple school website, it is hoped that teachers can use the website to build school profiling media to present themselves in the world of online portals.